Health promotion programs in prison: attendance and role in promoting physical activity and subjective health status - Tesler, Riki; Regev, Ofer; Birk, Ruth; Barak, Sharon; Shapiro, Yair; Weiss, Yossi; Zigdon, Avi; Ben Zvi, Kathrin; Vaknin, Yochanan; Green, Gizell; Sohlberg, Idit; Zwilling, Moti; et al. (Frontiers in Public Health, 2023)
Maintaining inmate health can serve as a challenge due to unhealthy background, risky behavior, and long imprisonment. This study aimed to analyse the prevalence of participation in health promotion activities among Israeli inmates and its association with their physical activity levels and subjective health status. A cross-sectional study was designed to examine 522 inmates (429 males, 93 females). The data were collected by trained face-to-face interviewers and self-report questionnaires. Most of the participants (82.37%) did not meet the recommended physical activity level. Half of the participants reported that their physical activity levels decreased since they were in prison compared with 29.50% who reported that their physical activity levels increased. Physical activity and subjective health status were significantly higher among younger male inmates. Furthermore, participation in health-promoting activities was associated with higher levels of physical activity and subjective health status. Health promotion activities may play an important role in addressing the challenges of maintaining inmate health. Implications of the findings are further discussed.